ANALYZING THE EFFECTS OF FOREIGN OWNERSHIP AND INTELLECTUAL CAPITAL ON THE PERFORMANCE OF NON-CYCLICAL CONSUMER COMPANIES: THE MEDIATING ROLE OF R&D - Istiani, Tia; Rani, Puspita (Universitas Muhammadiyah Tangerang, 2024)
In the midst of increasingly fierce competition, companies in the consumer non-cyclical industry must develop effective strategies to maintain and improve company performance. Performance is an important thing that needs to be achieved by every company, because performance is a reflection of the company's ability to manage and allocate resources. This study aims to test Foreign Ownership and Intellectual Capital on Financial Performance and R&D Research methods used quantitative methods. The technical analysis used in this study is panel data regression. The tool used in this panel data regression is Eviews. The population in this study of Consumer Non-Cyclical sector companies on the Indonesia Stock Exchange for the 2019-2022 period is 124 companies. The sample of this study used the purposive sampling method of 15 companies. H1 rejected foreign ownership does not have a significant positive effect on company performance H2 accepted intellectual capital has a significant positive effect on company performance H3 accepted research & development is able to moderate strengthens the positive influence between foreign ownership on company performance H4 rejected research & development is unable to moderate strengthens the positive influence between intellectual capital relations on company performance, 1). Small, diversified foreign shareholdings can reduce the direct impact on a company's performance. 2). Employees who have a high level of expertise and skills can increase company productivity. 3). R&D accompanied by foreign ownership that contributes to it helps companies to better identify and manage risks. 4). R&D needs to be well focused to increase the positive effects of intellectual capital owned.